2022
DOI: 10.1007/s10899-022-10139-1
|View full text |Cite
|
Sign up to set email alerts
|

Using artificial intelligence algorithms to predict self-reported problem gambling with account-based player data in an online casino setting

Abstract: In recent years researchers have emphasized the importance of artificial intelligence (AI) algorithms as a tool to detect problem gambling online. AI algorithms require a training dataset to learn the patterns of a prespecified group. Problem gambling screens are one method for the collection of the necessary input data to train AI algorithms. The present study’s main aim was to identify the most significant behavioral patterns which predict self-reported problem gambling. In order to fulfil the aim, the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 70 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Sociodemographic characteristics in our sample were quite similar to those in other studies ( 41 , 63 ) and the prevalence of GD in our initial sample (23%) was comparable to other studies combining player tracking data and GD measures (18 - 27%, 27 29 ), suggesting a representative sample. In addition, we relied on self-report data, which is subject to recall bias.…”
Section: Discussionsupporting
confidence: 88%
“…Sociodemographic characteristics in our sample were quite similar to those in other studies ( 41 , 63 ) and the prevalence of GD in our initial sample (23%) was comparable to other studies combining player tracking data and GD measures (18 - 27%, 27 29 ), suggesting a representative sample. In addition, we relied on self-report data, which is subject to recall bias.…”
Section: Discussionsupporting
confidence: 88%
“…After screening the titles and abstracts, we deemed 44 records as potentially eligible for inclusion. From these, we excluded 26 for not meeting the eligibility criteria: 17 were not sufficiently related to the gambling field (e.g., Kim & Werbach, 2016;Uusitalo et al, 2021), 7 lacked a discussion of risks and/or ethical concerns (e.g., Auer & Griffiths, 2023;McAuliffe et al, 2022), and 4 were unidentified duplicates. We selected 16 studies to include in the final review.…”
Section: Resultsmentioning
confidence: 99%
“…Player data and AI support a variety of commercial use-cases including recommendation systems, fraud detection, and customer relationship marketing (Auer & Griffiths, 2023;Chui et al, 2018). They also assist stakeholders to curb the potential negative impacts of gambling (Ghaharian et al, 2022).…”
Section: Gambling Data and Artificial Intelligencementioning
confidence: 99%
“…Two recent studies [28, 29] moved toward rectifying these problems, recruiting large samples of online gamblers and asking them to complete the Problem Gambling Severity Index (PGSI) [30]. Both studies found that machine learning models yielded good classification performance when predicting PGSI scores from online gambling behaviours (area under the receiver operating characteristic curve [AUCs] ≈ 73%; see Model performance assessment below).…”
Section: Introductionmentioning
confidence: 99%